Mongolia - Promoting Investment and Job Creation : An Investment Climate Assessment and Trade Integration Study - World Bank (Washington, DC, 2012)
The aim of this report is to identify a set of concrete steps that the government of Mongolia might take to promote private-sector activity and greater integration with the global economy in a way that leads to job creation, broad-based growth and most importantly, poverty reduction. It does this by combining an assessment of the investment climate faced by firms (through analyses of firm and household surveys and supply chains in selected sectors) with a diagnostic trade integration study. The report is structured as follows. The second chapter lays out the context and background and describes some recent trends that give some indications of where things stand. This is followed in the third and fourth chapters, which constitute the core of the report, by a detailed mapping of the main aspects of the business environment and the setting for trade. The focus in these chapters is on the aspects of the business environment that most need improvement, and on the barriers to trade integration that are the most severe. The fifth chapter lays out the basic diagnosis. The sixth and seventh chapters then outline what the analysis indicates as the most important steps that need to be taken to improve the business environment and facilitate trade integration.